Radiocarbon ages of NW Himalaya peat record during 4.2 ka event - Dharmendra Pratap Singh; Kaustav Paul; Rahul Pawar; Soni Rai; Ranjan Kumar Mohanty; Amzad Hussain Laksar; Abhayanand Singh Maurya (PANGAEA, 2026)
This dataset contains high-resolution geochemical measurements from the CT-02 alpine peat profile collected from the Chandra Valley, northwestern Himalaya, Himachal Pradesh, India (32.472022° N, 77.612433° E; 4309 m a.s.l.). The 44 cm peat sequence spans approximately 5.6 to 1.0 ka BP and was sampled at 1 cm intervals. The chronology is constrained by six AMS radiocarbon dates obtained from bulk peat organic carbon and calibrated using the IntCal20 calibration curve; an age-depth model was constructed using the Bayesian Bacon approach.